INOVASI PEMBELAJARAN DI PESANTREN SALAF AL-FALAH (Studi Pada Pesantren Berbasis Keterampilan Hidup Dengan Penanaman Sikap Nasionalisme Di Kabupaten Bandung) - Ahmad Khori; Enco Mulyasa (Media Nusantara, 2018)
The forerunner of formal education departing from Islamic boarding schooleducation in this study raised life skills education in salaf boarding schools,talent coaching and interest of santri this paper can be used as a guide for theparties manager salaf ’s Islamic boarding school in educating life skill in scopesalaf ’s Islamic boarding school. From the results of the study can be obtainedinformation that education life skill is process develop, coach and excavation oftalent interest of santri, so after graduating from Islmic boarding school havecompetitiveness such as proficient trade, tahfidz, qiro’ah, honest, sincere, simple, independent, caring, free in acting but responsible for his actions, meticulous or careful and have commitment in doing good. implementation in daily life is done through three strategis, that is holdimg a little alpha in environment’s Islamic boarding school, makes unit –unit bussines by empowering santri who are in formal schooling, and determation the rule for citizens who are in the boarding school environment even outside Islamic boarding school. Always put forward humble atitute, model atitute from male teacher or female teacher result learning in the class can be implementatiaon directly with the hope that the potencialtha exist in the santri can be channeled with management Islamic boarding school which have been in the stackimg by a buffer and teachers involved in it.